If it's not what You are looking for type in the equation solver your own equation and let us solve it.
-6=n/2-10=
We move all terms to the left:
-6-(n/2-10)=0
We get rid of parentheses
-n/2+10-6=0
We multiply all the terms by the denominator
-n+10*2-6*2=0
We add all the numbers together, and all the variables
-1n+8=0
We move all terms containing n to the left, all other terms to the right
-n=-8
n=-8/-1
n=+8
| 4d+6=d-6 | | 14x+4x=2-2x | | 3(x+5)=7x-9 | | -1+2m+6=-1 | | 4(5x-90)=2(x+54) | | 9x-33=7x+17 | | 4x+5+2=15 | | 2x+(3x-7)=8 | | k+5/3=7/4 | | -5m+3m=-2 | | 3a-30=-6 | | 1/3(6x-12)=-34 | | -5m+3m=-2* | | 3x+4(2x+10)=13 | | X+9=11-2x | | 3x+4(2x=10)=13 | | 2(1.5+2x)+2x=15.6 | | 2/3(7x-6=44/3 | | 2.64t+4t=12 | | 5(-3x-7)+(3x+21)= | | 0,8x+24=1.2x+30 | | 176=3-v | | -20n-28=10n+2 | | 4x-37=7 | | 121-x=175 | | x-4/4=2/3(x+3)-8 | | -31/3x-4/5=22/3 | | b+4+b=-2 | | 2x+5-(3x-4)=-2x+8 | | -20-28=10n+2 | | 2=2-8v+8v | | 4x+5=5x+45 |